Brick Powder, an Effectual Adsorbent for the Exclusion of Cr(VI) Ion from Aqueous Solution - Bohara, Gauri; Pradhanang Shrestha, Situ; Nyachhyon Rajbhandari, Armila (Amrit Journal, 2025)
The adsorption efficiency of finely grinded brick powder on the exclusion of chromium (VI) from the aqueous solution using various experimental situations was successfully assessed. Batch adsorption studies demonstrated the uptake of chromium ions at an assortment of different pH values, adsorbent dosages, contact time and initial concentration of metal ion. Contact time for maximum adsorption required was 120 min at pH 2 with agitation speed 160 rpm and 1 g was optimum dose for adsorption. The maximum adsorption capacity (Qm) of brick powder was found 82.64 mg/g. The investigational data were snug well with Freundlich isotherm as compared to Langmuir isotherm and Temkin isotherm models. Freundlich model showed heterogeneous multilayer adsorption on brick powder. Freundlich constant n value was found to be 1.35, indicating a heterogeneous surface and favors a physical process of adsorption. Positive Tempkin constant value signifies an exothermic process where adsorption is favored by lower temperatures and heat is released as molecules attach to the surface. The Tempkin constant value < 20 kJ/mol is also evidence of physical adsorption.